Moving a data center keeping availability at the top - Chierici, Andrea; Michelotto, Diego; Sergi, Giusy; Pascolini, Alessandro; Lattanzio, Daniele (EPJ Web of conferences, 2025)
We are moving INFN-T1 data center to a new location. In this document we will describe all the steps taken to complete the task without decreasing the general availability of the site and of all the services provided.